Šport, mitologija in genealogija junaštva - Šaver, Boštjan (Monitor ISH, 2006)
The image of a hero has always served to transmit the dominant ideology and reproduce the existing social order. The paper analyses the implicit structures linking the institution of sport to other dimensions of society, such as religion, culture, the media, or politics. The social construct of the athlete as hero is most explicit in the following aspects of sport: sport as a collective activity, as popular culture and as a media narrative, as religion and ritual, as myth, and as a form of war. An outstanding blend of these aspects is achieved in the phenomenon of the Olympic Games, ancient and modern, which have established the figure of the athlete as hero even - indeed, primarily - in contemporary society.
Keywords: ideologija; culture; kultura; junaki; heroji; sport; šport; olimpijske igre